The colonial and national formations of the National College of Arts, Lahore, circa 1870s to 1960s : de-scripting the archive - Tarar, Nadeem Omar (Anthem Press, 2022)
Lahore's Mayo School of Arts, as the National College of Arts (NCA) was called then, was Pakistan's equivalent of London's South Kensington School of Design (presently Royal College of Art, UK). One of the last of the four colonial art schools established in India, the others being in Calcutta, Bombay and Madras, the Mayo School of Arts was founded in 1875 to perpetuate the memory of the Lord Earl of Mayo, the only Indian Viceroy to be murdered while in office. Established by Rudyard Kipling's father Lockwood Kipling, the school had on its staff some of the most renowned names in the Indian art world, such as Ram Singh, Percy Brown, Lionel Heath, S. N. Gupta, B. C. Sanyal and A. R. Chughtai. The Mayo School gave birth to the most celebrated Indian art historical publication in the world, the Journal of Indian Art and Industry. The pioneers of colonial anthropology in Punjab, the fabled 'men on the spot', such as Richard Temple, Denzil Ibbetson and Baden Powell, were associated with the establishment and administration of the Mayo School of Arts. Through its pedagogy, the Mayo School also framed the emergence of the Indo-Saracenic school of architecture and patronized the traditional styles of paintings in Punjab. In the founding decades of Pakistan, to mark the cultural transition from a colonized to an independent national identity, the 'old' Mayo School was reorganized and raised as the National College of Arts in 1958. To reflect its role in developing national culture and imparting professional visual art education, the NCA was established on the model of Bauhaus with three main departments in fine art, design and architecture.